Examining the moral obligation of healthcare workers through a Kantian lens - Tan, Carmen Tien Min (Nanyang Technological University, 2022)
The moral obligations of Healthcare Workers (HCWs) have been a trending topic of debate in recent times, especially with the rise in pandemic crises. These discussions, however, have addressed HCWs moral obligations independently rather than accessing them in accordance with a larger perspective. HCWs are presently embodied in large-scale healthcare institutions, with many other considerations to be factored in when we attempt to address their moral obligations. Presently, many have discussed the benefits of using Kantian Ethics in modern healthcare. As such, this paper aims to address the insufficiency in upholding Kant’s moral framework in attempting to account for the moral obligations of HCWS in the modern healthcare system. My objections are as follows: Kantian ethics is unable to account for firstly, what ‘duty to care’ entails and secondly, the significance of motives other than concern for the patient that influence HCWs in performing their duty to care. In response to potential objections in my paper, I also discuss the issues of Kant’s intent on pivoting rationality as the cornerstone of human moral worth. Though I address potential objections my proposal, I will show that these objections ultimately fail. As such, I conclude that it is ineffectual for us to look to Kant in addressing the moral obligation of HCWs, especially in modern times.